PENGARUH KEPUASAN, KEPERCAYAAN DAN KOMITMEN TERHADAP LOYALITAS PELANGGAN ( Studi Kartu Perdana XL pada Mahasiswa Universitas Stikubank Semarang ) - Yusuf Rifki Mahardika, 08.05.51.0057; Kasmari, Kasmari (Students Journal of Economic and Management, 2012)
The purpose of this study was to determine the effect of satisfaction, trust and commitment to customer loyalty. Based on the research goal is to take title "The Effect of Satisfaction, Trust, Commitment to Customer Loyalty (Studies XL On SIM Card Stikubank Semarang University student))". Population research on student stikubank Semarang and sampled 80 respondents. Study using primary data by questionnaire. Data analysis using regression analysis. Results were positive and significant effect of satisfaction on loyalty. So that if customer satisfaction XL card up, it will create will also increase customer loyalty. Significant positive influence of trust and loyalty. So that if trust customers of XL card up, it will create will also increase customer loyalty. Commitment and a significant positive effect on customer loyalty so that when commitment to XL card up, it will create high customer loyalty. Satisfaction, trust and commitment are jointly significant and positive effect on customer loyalty, so if satisfaction, trust and commitment together will make up the high customer loyalty. Adjusted R Square 51.1% can be explained by satisfaction, trust and commitment to loyalty. While the remaining 48.9% are explained by other variables of satisfaction, trust, commitment a competitors and quality of service.Keywords: Satisfaction, Trust, Commitment and Loyalty